Prevalence and factors associated with gambling disorders among in-school adolescents in a rural community in South-Western Nigeria (2022)
Background: Gambling rates are increasing among adolescents in rural communities. Our study aimed to determine the prevalence, patterns, and factors associated with gambling disorders, among in-school adolescents in a rural community in South-western Nigeria. Materials and methods: The study was crosssectional in design involving 427 adolescents selected by a two-stage sampling method across secondary schools in Igbo-Ora. A questionnaire developed from literature and “The South Oaks Gambling Screen-Revised Adolescent Questionnaire” was used to obtain information on sociodemographic and behavioural characteristics and gambling practices. Results: The mean age of the respondents was 14.0 ± 2.2 years with a little over half (51.3%) in the mid to older adolescent age group (14-17 years). The most common forms of gambling reported were playing dice games (46.0%), throwing rubber bands (42.5%), and card games (41.6%) for money. The odds of males ever gambling were two times more than females gambling (OR=2.43, 95%CI: 1.54-3.83). Conclusion: Gambling and problem gambling among adolescents in rural areas is high. Males and adolescents who use alcohol tend to gamble more. Multi-pronged interventions through education, youth-friendly programmes which will complement cultural values are recommended. There’s also a need to inculcate rehabilitation services at primary health care facilities in rural areas to manage adolescents who are problem gamblers.